2022
DOI: 10.1186/s13567-022-01025-0
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever virus MGF360-11L negatively regulates cGAS-STING-mediated inhibition of type I interferon production

Abstract: The type I interferon (IFN-I) signaling pathway is an important part of the innate immune response and plays a vital role in controlling and eliminating pathogens. African swine fever virus (ASFV) encodes various proteins to evade the host’s natural immunity. However, the molecular mechanism by which the ASFV-encoded proteins inhibit interferon production remains poorly understood. In the present study, ASFV MGF360-11L inhibited cGAS, STING, TBK1, IKKε, IRF7 and IRF3-5D mediated activation of the IFN-β and ISR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…On the other hand, multiple viral proteins targeting the same molecules/innate immune pathways and providing functional redundancy are commonly observed and have been extensively reported for large DNA viruses such as ASFV and VACV. Degradation of TBK1 by ASFV I215L ( 26 ) and ASFV MGF 360-11L ( 32 ) and NF-κB inhibition by A238L, the homolog of IκB ( 80 ), and I215L ( 27 ) are a few examples of ASFV protein functional redundancy. In contrast, ASFV I215L is involved in the virus replication cycle ( 81 ) and host protein synthesis ( 82 ), and MGF 360-11L degrades IRF7 ( 32 ), which are nonredundant functions of ASFV proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, multiple viral proteins targeting the same molecules/innate immune pathways and providing functional redundancy are commonly observed and have been extensively reported for large DNA viruses such as ASFV and VACV. Degradation of TBK1 by ASFV I215L ( 26 ) and ASFV MGF 360-11L ( 32 ) and NF-κB inhibition by A238L, the homolog of IκB ( 80 ), and I215L ( 27 ) are a few examples of ASFV protein functional redundancy. In contrast, ASFV I215L is involved in the virus replication cycle ( 81 ) and host protein synthesis ( 82 ), and MGF 360-11L degrades IRF7 ( 32 ), which are nonredundant functions of ASFV proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of TBK1 by ASFV I215L ( 26 ) and ASFV MGF 360-11L ( 32 ) and NF-κB inhibition by A238L, the homolog of IκB ( 80 ), and I215L ( 27 ) are a few examples of ASFV protein functional redundancy. In contrast, ASFV I215L is involved in the virus replication cycle ( 81 ) and host protein synthesis ( 82 ), and MGF 360-11L degrades IRF7 ( 32 ), which are nonredundant functions of ASFV proteins. In vaccinia virus (VACV), C4 and C16 proteins bind to lupus Ku autoantigen protein p70 (Ku70) to antagonize DNA-PK by binding to Ku and blocking Ku binding to DNA, reducing the production of cytokines and chemokines ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the cGAS-STING-mediated DNA-sensing signal is crucial for host defence against many viruses, especially DNA viruses, few viral components have been identified that specifically target this signaling pathway ( 9 ). Many human oncogenic viruses such as human papillomavirus (HPV) ( 1 , 10 13 ), many DNA viruses such as herpesvirus, pseudorabies virus ( 14 ), avian oncogenic herpesvirus ( 15 ), poxviruses such as fowlpox virus ( 16 ), and asfarviruses such as African swine fever virus ( 17 20 ) are known to be recognized by host pattern-recognition receptors and have been shown to subvert the cGAS-STING signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, some key proteins of the IFN pathway are the target of multiple ASFV inhibitors. For instance, TBK1 is inhibited (or degraded) by E120R ( Liu H. et al, 2021 ), DP96R ( Wang et al, 2018 ), MGF-360-11L ( Yang et al, 2022 ), and A137R ( Sun et al, 2022 ). Similarly, JAK/STAT are targeted by MGF-360-9L ( Zhang et al, 2022 ) and MGF-505-7R ( Li et al, 2021b ).…”
Section: Viral Antagonism Of Interferon and Nuclear Factor κB Pathway...mentioning
confidence: 99%